2002
DOI: 10.1016/s0022-5347(05)64621-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Osteopontin in Rat Kidneys: Induction During Ethylene Glycol Induced Calcium Oxalate Nephrolithiasis

Abstract: In response to exposure to oxalate and calcium oxalate crystals renal epithelial cells increase the production of osteopontin, which may have a significant role in calcium oxalate nephrolithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 24 publications
3
56
2
1
Order By: Relevance
“…Additionally, Hyperoxaluria could significantly up-regulate OPN expression and further promote its secretion after crystal deposition in kidneys. Simultaneously, a concomitant increase was found in urine [41]. In current study, even though the model induced by 5%AmO x differed from by ethylene glycol, significant elevation of OPN in both urine and kidney was observed in the control group.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Additionally, Hyperoxaluria could significantly up-regulate OPN expression and further promote its secretion after crystal deposition in kidneys. Simultaneously, a concomitant increase was found in urine [41]. In current study, even though the model induced by 5%AmO x differed from by ethylene glycol, significant elevation of OPN in both urine and kidney was observed in the control group.…”
Section: Discussionsupporting
confidence: 40%
“…The underlying mechanisms may be Values are expressed as mean ± SD, * P \ 0.05 when compared to the control, ** P \ 0.05 when compared to the normal related to their abundant flavonoid constituents, which as antioxidants inhibit oxidative stress response so as to down-regulate OPN expression indirectly. Khan SR et al [41] revealed that with the CaO x crystal formation, particularly after crystal deposition, OPN expression in the kidney gradually expanded from the loop of Henle and papillary surface epithelium to the whole renal tissue section. We also observed OPN weak expression in normal rats and strong expression in urolithiatic rats.…”
Section: Discussionmentioning
confidence: 99%
“…With various coworkers, I have studied many aspects of urolithiasis in male and female SpragueDawley rats. [26][27][28][29][30][31][32] When hyperoxaluria is induced by administration of 0.75%-1% EG, there is an increase in urinary excretion of Ox within 2 days, hyperoxaluria is established within 3 days, CaOx crystalluria develops within 2 weeks, and CaOx nephrolithiasis develops within 4-6 weeks. 23 Urinary pH and excretion of citrate are significantly decreased.…”
Section: Animal Model Studiesmentioning
confidence: 99%
“…CaOx crystal deposition in the kidneys increases the expression of Tamm-Horsfall protein (THP), 41,42 osteopontin (OPN), 30 inter-alpha-inhibitor (ITI), 31,32 prothrombin Urine was collected once a week. After 1 week of treatment, the nephrolithic rats on diets with EG excreted significantly more (P Ͻ 0.05) arachidonic acid (AA) and prostaglandin E2 (PGE) in their urine than three control male rats on a normal diet.…”
Section: Animal Model Studiesmentioning
confidence: 99%
“…Crystal-cell adhesion and dislocation are other mechanisms which are thought to be involved in stone formation [36,37]. These processes are strongly influenced by numerous factors which include the presence or absence of different types of urinary components which can be up-or down-regulated in the presence of endogenous or exogenous stimuli [38,39]. Perhaps stress might be an influential factor in this regard.…”
Section: Discussionmentioning
confidence: 99%